Rodents and insectivores from the Lower Miocene (Agenian and Ramblian) of the Tudela Formation (Ebro Basin, Spain) - Ruiz-Sánchez, F. Javier; Murelaga, X.; Freudenthal, M.; Larrasoaña, J. C.; Furió, M.; Garcés, M.; González-Pardos, M.; Suárez-Hernando, O. (Journal of Iberian Geology, 2012)
Rodents and insectivores from the Lower Miocene (Agenian and Ramblian) of the Tudela Formation (Ebro Basin, Spain)